The Influences of Conflicts toward Social Aspects in The Casual Vacancy novel by J. K. Rowling - Eka Puspita Sari; Wahyuni (Faculty of Letters Universitas Balikpapan, 2023)
This thesis explores the influences of conflicts toward social aspects in The Casual Vacancy novel by J. K. Rowling. There are two objectives of this research; 1) To find out the forms of conflicts int the novel The Casual Vacancy by J. K. Rowling and 2) To explain the conflicts influences the social aspects in the novel The Casual Vacancy by J. K. Rowling. In researching a literary work related to social. The researcher uses Sociology of Literature approach, conflict theory by Lewis Alfred Coser and Social Aspects. The methodology in this study is qualitative research by taking data from quotations in the novel which the researcher conveys descriptively. The result of this research is internal conflict showing the conflict influences the social aspects, it is social relationship. The second result of this research is internal conflict showing the conflict influences the social aspects, it is criminality. Conflict that occurs between two different groups, which will strengthen the conflicting group by providing clear boundaries with other groups. These two conflicts influence social aspects with insignificant result. It means a way of viewing situation, condition and issues in the society can show internal and external conflicts in daily life.